(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
Analysis of the Implementation of the Online Academic Information System (SIAKAD) at Muhammadiyah University Jakarta. Public Administration Study Program, Faculty of Social and Political Sciences, Muhammadiyah University Jakarta. The focus of this research is to find out and measure the application of the SIAKAD Online academic information system at Muhammadiyah University Jakarta to be better, more effective and efficient. The information gathering strategy used in this study was to disseminate questionnaires to be able to obtain data from respondents. The instrument used in this study was a questionnaire while the variable used in this study was the independent variable, namely the quality of academic services (X) and the dependent variable was student satisfaction (Y). In processing, the first step is to test the validity and reliability of the questionnaire. Validity test is used to test the instrument so that it gives results according to its purpose. Singarimbun and Effendi (1995) suggest that validity indicates the level of ability of the research instrument to measure what is desired and to be able to reveal the data and variables studied appropriately. After testing the validity, then the questionnaire used needs to be tested for reliability to show the consistency of the measuring instruments used in the study. A reliable questionnaire is a questionnaire which, if tried repeatedly on the same group, will produce the same data. According to the United Nation in Budiati (2003:21), states that there are 7 key factors in the implementation of e-Government.